Investor Protection Model in Digital Retail SBSN with Sharia Compliance Assurance - Sahdani Ritonga; Ramlan Ramlan; Muhammad Arifin (JURNAL AKTA, 2026)
This study aims to analyze and develop an investor protection model in Digital Retail Sovereign Sukuk (SBSN) within the context of digital financial service transformation. The increasing use of digital platforms in retail sukuk distribution has introduced new challenges in investor protection, particularly regarding the adequacy of risk disclosure, the effectiveness of complaint handling mechanisms, and the assurance of sharia compliance in digital transactions. The research employs a socio-legal research approach with qualitative descriptive analysis. The data used are secondary legal materials consisting of laws and regulations on sovereign sukuk, financial technology governance, financial consumer protection, and sharia compliance frameworks. Data collection was conducted through document analysis, while data analysis was performed using qualitative legal interpretation to identify gaps between normative regulation and its implementation in the digital retail SBSN ecosystem. The novelty of this study lies in the formulation of an integrated investor protection model that combines standardized digital risk disclosure, an integrated complaint and dispute resolution system, and a structured sharia compliance assurance mechanism that is auditable and transparent within the digital distribution process. The study concludes that effective investor protection in Digital Retail SBSN requires the strengthening of standardized risk communication, the establishment of a unified complaint handling system with clear escalation procedures, and the implementation of an accountable sharia compliance assurance framework. These components collectively enhance legal certainty, transparency, and investor trust in the digital sovereign sukuk market.